The Secret of the Explosive Nature of the Aurora - Akasofu, Syun-Ichi (European Journal of Applied Sciences, 2022)
The aurora is basically an electrical discharge phenomenon in space around the earth. After the introduction of satellites in this subject, auroral science has greatly advanced. This article describes the present understanding the aurora and its explosive nature from the point of view of a series of electrical discharging processes, namely power supply (dynamo), circuit/current and dissipation (auroral phenomena); this is rather a new approach in the search for the secret of the aurora; in the past, many efforts have been focused on moving magnetic field lines. It is shown that the discharge circuit accumulates the power after the dynamo power increases above 1011 w, but it becomes unstable when the accumulated power becomes about 1016 J, thus suddenly unloading it and generating spectacular auroral displays.